Developing receptive skills in two modern languages: some facilitating and hindering factors (2010)
The present paper describes the findings concerning the receptive skills (listening and reading) in two modern languages (English and Ukrainian) of ten-year-old Hungarian children living in a minority context in Ukraine. The study was conducted in Transcarpathia (Zakarpatska oblast – Закарпатська область), an administrative region in south-western Ukraine, where about 150,000 Hungarians live in a minority context. Berehovo is a small town in the west of Transcarpathia with a population of 26,000 people. Forty-eight percent of the inhabitants are Hungarians (Molnár and amp; Molnár, 2005). There are four Hungarian schools in the town where the first phase of our longitudinal study was conducted in the 2006/2007 school year.